Diagonalizability theorem for matrices over certain domains - Zabavsky, B.; Domsha, O. (Algebra and Discrete Mathematics, 2011)
It is proved that R is a commutative adequate domain, then R is the domain of stable range 1 in localization in multiplicative closed set which corresponds s-torsion in the sense of Komarnitskii.